Divergent Roles of Antiself Antibodies during Infection. Issue 7 (July 2018) - Rivera-Correa, Juan; Rodriguez, Ana
Abstract : Antiself antibodies are most commonly associated with autoimmune disorders, but a large body of evidence indicates that they are also present in numerous infectious diseases. These autoimmune antibodies appear transiently during infection with a number of viruses, bacteria, and parasites and in some cases have been associated with the development of autoimmune disorders that develop after infection has been cleared. Traditionally these infection-associated autoantibodies are considered an erroneous byproduct of a legitimate immune response, but their possible role in the clearance of microbes and infected cells or inhibition of host-cell invasion suggests that they may be present because of their beneficial protective role against various infections. Highlights: Antiself antibodies are frequently generated during several viral, bacterial, or parasitic infections. Infection-induced antiself antibodies may lead to transient autoimmune pathology or persistent autoimmune disorders after infection is cleared. Antiself antibodies may also contribute to protection from infection by interfering with host-cell invasion and/or by facilitating the detection and elimination of infected cells. Given their potential contribution to pathogen clearance, the generation of infection-induced antiself antibodies may be part of a normal response and not merely an erroneous immune reaction.